Common writing challenges in academic English among Chinese nursing undergraduates - Bartlomiej Kuszel (Erudita: Journal of English Language Teaching, 2025)
The study examines the most common writing challenges in Academic English faced by Chinese undergraduate nursing students. Despite meeting the general English proficiency benchmark of College English Test Band 4, many students struggle with the academic writing conventions necessary for success in university and professional nursing contexts. The analysis was based on writing samples taken throughout the term from 38 second-year nursing students from a university in Northwest China. The mistakes were categorised according to Ferris' taxonomy of errors (1995, 2002, 2012). Results show that surface-level errors, including punctuation, spelling, and mechanics, were the most common, accounting for more than one-third of all errors. However, more profound grammatical issues, particularly errors in verb form, collocation mistakes, and article omissions, had a greater impact on clarity and academic tone. The findings suggest that many errors stem from interference with the first language (L1). This study emphasises the importance of instructional strategies that focus on verb use, sentence structure, and genre-appropriate vocabulary. The article discusses practical approaches to English for Academic Purposes (EAP) instruction.